Rescue Augmentation: Increased Stability in Augmentation After Initial Loosening of Pedicle Screws. Issue 5 (June 2021) - Weiser, Lukas; Huber, Gerd; Sellenschloh, Kay; Püschel, Klaus; Morlock, Michael M.; Viezens, Lennart; Lehmann, Wolfgang
Study Design: Biomechanical study. Objectives: Failure of pedicle screws is a major problem in spinal surgery not only postoperatively, but also intraoperatively. The aim of this study was to evaluate whether cement augmentation may restore mounting of initially loosened pedicle screws. Methods: A total of 14 osteoporotic or osteopenic human cadaveric vertebral bodies (L2)—according to quantitative computed tomography (QCT)—were instrumented on both sides by conventional pedicle screws and cement augmented on 1 side. In vitro fatigue loading (cranial-caudal sinusoidal, 0.5 Hz) with increasing peak force (100 N + 0.1 N/cycles) was applied until a screw head displacement of 5.4 mm (∼20°) was reached. After loosening, the nonaugmented screw was rescue augmented, and fatigue testing was repeated. Results: The fatigue load reached 207.3 N for the nonaugmented screws and was significantly ( P = .009) exceeded because of initial cement augmentation (300.6 N). The rescue augmentation after screw loosening showed a fatigue load of 370.1 N which was significantly higher ( P < .001) compared with the nonaugmented screws. The impact of bone density on fatigue strength decreased from the nonaugmented to the augmented to the rescue-augmented screws and shows the greatest effect of cement augmentation on fatigue strength at low bone density. Conclusions: Rescue augmentation leads to similar or higher fatigue strengths compared with those of the initially augmented screws. Therefore, the cement augmentation of initially loosened pedicle screws is a promising option to restore adequate screw stability.